Stovepoint / Muhammad Amel Feryal Rini Fauzan - Rini Fauzan, Muhammad Amel Feryal (Universiti Teknologi MARA, Kedah, 2025)
STOVEPOINT is a modular, sustainable, and user-centered solution designed to address the cooking challenges faced by displaced populations in humanitarian settings, such as refugee camps and disaster relief zones. These environments are often characterized by limited space, inadequate cooking infrastructure, and reliance on unsafe or environmentally harmful methods, such as open fires. This project aims to create a compact and energy-efficient electric cooker station, emphasizing modularity, adaptability, and sustainability. The design incorporates energy-efficient technologies to ensure environmental responsibility while meeting the immediate needs of users. Research methods included an in depth review of academic articles and industry reports to understand the limitations of existing cooking solutions and explore innovative design strategies. Additionally, surveys were conducted to gather insights into user preferences and challenges , ensuring a practical and relevant design. STOVEPOINT’s modular structure allows it to adapt to varying user needs and space constraints enhances accessibility in resource-limited environments. By integrating these features, the electric cooker station not only provides a safe and efficient cooking solution but also contributes to the well being of displaced populations and promotes long term sustainability. This project highlights the potential of design innovation to address humanitarian challenges , fostering resilience and improving quality of life for vulnerable communities.